Correlation of Knowledge and Public Attitude With Vaccination Covid-19 Injection at Sub-Discrit Tuwelei of Tolitoli Regency - Herawati; Eka Prasetia Hati Baculu (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
At sub-district tuwelei of tolitoli regency, there are still many society members who are afraid of covid-19 vaccination, this case can be seen from data obtained by researcher who said that a number of public who did not want to be vaccinated are greater than those who wanted to be vaccinated. This was caused bey some affecting factors such as, afraid of being injected, prosses heredity disease and some respondents expressed their worries toward safety of vaccination and stated their unbelives toward covid-19 because of the presence of issue that covid-19 is only deceit of health staffs, the objective of this research to find out correlation of knowledge and public attudes with the gift of covid-19 vaccination at sub-disrict tuwelei. This research is a kind of analytical survey method using cross sectional approach. Sample selection In this research used proportionate random sampling technique.sample selected in this research used proportionate random sampling technique. Sample selected is 99 public members of over 18 years old. Research finding show that there is no correlation of knpwledge and covid-19 vaccination which is proven by statistical test at value (p- value 0,051 < 0,05), on the other hand, there is correlation of attitudes with is proven by statistical test at value ( p-value 0,000 <0,05). This research suggested that education of covid-19 vaccination be necessarily increased and for public to participate in the prevention of covid-19 by vaccinated